Weaving gender, embroidering the Queer-po: The textile archive in muxe identity (Altre Modernità, 2024)
In recent years, the muxe identity has been gaining visibility in the city of Juchitán—in the Isthmus of Tehuantepec in the Mexican state of Oaxaca. Even before recent gender theories were disseminated, the muxe, people born with masculine attributes who assume feminine roles, have always been aware of belonging to a cultural expression outside the normative canons. Not necessarily self-perceived as transgender women and even less as members of a “third gender”, the muxe form a unique linguistic-aesthetic-cultural ecosystem that exists only in the Zapotec communities of the Isthmus. Persecuted by macho violence, the muxe struggle to break the stereotypical image of the feminine in which patriarchal society continues to confine them. Excluded from the labour market, many of them can only dedicate themselves to the embroidery of traditional gowns, the making of which has become a deeply identifying act that, on the one hand, recovers their indigenous roots and, on the other one, reaffirms their individuality as women. The legacy of pre-Hispanic craftsmanship and contemporary forms of queer corporeality find in the bright colours of the huipiles a textile archive in movement that, from the indigenous past, has been weaving, thread after thread, a history of struggles and rights.
Keywords: muxe; textile archive; third gender; queer; Zapotec culture